Quality Material and Project Cost (A study of Lagos State housing development Scheme) - Pelumi Rukayat; Olateju I; Awolaja K; Hammed Gazal (Research Synergy Press, 2022)
Material is a critical element in the construction project as it constitutes to a larger portion of the projects cost. It’s important to determine the degree of relationship between material and project costs. For this reason. This study tends to assesses the degree of relationship between quality material and project cost, A survey research design was used for this study. The sample size of this study was 105. The study used purposive sampling technique to select the choice of staffs. Primary data was used for the study and were gotten by the use of a structured questionnaire. To test the hypothesis, Pearson’s Product Moment Correlation coefficient was used. The results show that there is a strong positive relationship between quality material and project cost (r = 0.881). It was recommended among others that, the project managers, engineers and other stakeholders interested in housing development projects to implement the quality management actively to achieve efficient project cost.